The tower houses of County Kerry - McAuliffe, Mary (Trinity College (Dublin, Ireland). Department of History, 1992)
This thesis is a comprehensive study of the tower houses of County Kerry and there is also some reference to the earlier castles of Kerry. In volume 1 all aspects of the tower house are looked into. The tower houses are placed in their historical context in chapter 2 on the History of Kerry. In chapter 3, on the castle and the tower house, the relationship between the preceding stone structures, and other structures such as moated sites, and the tower house is looked at. In the fourth chapter the origins of the tower house are discussed; whether the tower house originated outside Ireland, or if there was a suitable climate, politically, economically, socially, and architecturally for the tower house to have an independent origin in Ireland. In chapter five the relatively controversial issue of the dating of tower houses as well as distribution is dealt with. The ways of dating a tower house and their reliability are looked at, as are the dates of tower houses in Ireland in general, and Kerry in particular. In the second part of this chapter the distribution of tower houses and the many factors affecting this distribution are looked at. In the sixth chapter the use or lack of use of the tower house in warfare, against thieves, withstanding sieges, and the use of the fastness in relation to the tower house is looked into. In chapter 7 the use of these structures as a residence is dealt with. Using many sources the type and quality of life to be expected in a tower house is discussed. In chapter 8 the architecture of the tower houses in Kerry is described, and in chapter 9 the few urban and church tower houses in Kerry are looked at. In chapter 10, the conclusion, the results of all the preceding chapters are summed up. In volume two the results of the fieldwork carried out are presented in the form of a catalogue. In this list is also included the early castles and the late 17th century / early 18th century "castles". The format of the catalogue includes the name of the structure, its location i.e. the barony and an estimate of the ordnance survey location using the half inch map; also the date, or possible date if known, and the family which built or owned the structure also if known. Then there are the references to the tower house or castles, in annals, early guide books, lists, parliamentary documents etc. and a brief summary of the 1841 Ordinance Survey description if it exists. Finally, there is a summary of the results of the author’s fieldwork on the existing tower houses and castles. Also in volume two are the plates, plans, and maps.
Keywords: History, Ph.D.; Ph.D. Trinity College Dublin